The Effect of Digital Storytelling on Student Engagement and Literacy Skills - Sitohang, Norenta; Hutagalung, Siti Nurhabibah (Literacy: Journal of Education and Social Science, 2024)
This study aims to determine the influence of digital storytelling on student engagement and their literacy skills. Digital storytelling, which combines narrative elements with multimedia technology, is expected to improve students' learning experience and enrich literacy skills, both in reading, writing, and critical thinking. In the context of education that is increasingly connected to technology, this approach is considered relevant to increase student motivation and participation in learning. This study uses a quantitative method with a pseudo-experimental design. The research sample consisted of students from several high schools divided into two groups: an experimental group that used digital storytelling in learning and a control group that used traditional methods. Data was collected through student engagement questionnaires and literacy skills tests adapted from the applicable curriculum. The data analysis technique uses a t-test to see the difference between the experimental group and the control group. The results showed that there was a significant increase in student engagement and literacy skills in the experimental group that used digital storytelling. Students who are involved in digital storytelling-based learning show higher motivation in following the learning process and better literacy skills, especially in the aspects of text comprehension and writing creativity. In contrast, the control group that used conventional methods did not show significant changes in both aspects. Based on these results, it can be concluded that digital storytelling has a positive influence on student engagement and their literacy skills. Therefore, the application of digital storytelling in learning can be one of the innovative alternatives to improve the quality of education in this digital era.